Preparation method of anhydrous proton conductive electrolyte material based on supramolecular metal halide framework
By constructing a supramolecular metal halide framework, using organic cations and halide ions to form a hydrogen bond network, the challenge of proton conduction at intermediate temperatures is solved, and anhydrous proton conductive electrolyte material with high conductivity is achieved, with competitive performance.
Patent Information
- Application Number
- CN202411836942.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-04
AI Technical Summary
At intermediate temperatures, proton conduction presents challenges in proton exchange membranes and direct methanol fuel cells, affecting the development and performance of anhydrous proton conductive electrolytes.
By constructing a supramolecular metal halide framework, a continuous hydrogen bond network is formed using appropriate organic cations and halide ions (I and Br) to achieve proton transfer. The specific method includes mixing Bi2O3, 4-Apy, saturated hydrohalogenic acid and ethanol, insulating it in an autoclave, and then washing it with anhydrous ethanol to obtain anhydrous proton conductive electrolyte material.
A water-free proton conductive electrolyte material with high conductivity has achieved a proton conductivity of 1.54×10−3S cm−1 at 140°C, which has competitive performance and shows a different proton conduction mechanism than proton conductive solids.
Smart Images

Figure CN119551719A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of anhydrous proton conductive electrolyte materials, and in particular relates to a preparation method and application of anhydrous proton conductive electrolyte materials based on a supramolecular metal halide framework. Background Art
[0002] Proton conduction at intermediate temperatures (100-200 °C) is a major challenge for proton exchange membranes (PEMs) and direct methanol fuel cells, making the development of anhydrous proton-conducting electrolytes essential. However, the local and translational motion of proton carriers strongly affects the proton transfer rate. To control the mobility of proton carriers, further support matrices, flexible organic polymers or high-porosity solids that provide space for carriers to move are considered promising. Organic-inorganic metal halides (OIMHs) are a class of semiconductor crystalline materials composed of organic cations and inorganic frameworks. The organic cations in OIMHs are proton carrier molecules, and the presence of halogens on the inorganic framework can provide an ideal hydrogen bonding network for proton-carrier molecules, which have high mobility and show a suitable stacking structure. We propose that OIMHs are excellent candidates for anhydrous proton conductors. Summary of the invention
[0003] Appropriate organic cations and halogen ions (I and Br) in the inorganic framework can construct a continuous hydrogen bond network for proton transfer. Due to the different interactions between organic cations and halogen ions, (4-Apy)BiI4, (4-Apy)BiI 3.27 Br 0.73 The conductivity measurements of (4-Apy)BiBr4 at different temperatures and under anhydrous conditions show different curves. Among them, the high conductivity of (4-Apy)BiI4 (σ = 1.54×10 at 140°C) −3 S cm −1 ) are competitive with several best-performing anhydrous proton-conducting MOFs / PCPs. The systematic results based on SMHFs suggest that proton conduction is a new backbone for metal halide materials and a different approach to proton-conducting solids.
[0004] A method for preparing an anhydrous proton conductive electrolyte material based on a supramolecular metal halide framework comprises the following steps: (1) Bi2O3, 4-Apy, saturated hydrohalic acid and ethanol are uniformly mixed to obtain a mixture A; (2) adding the mixture A obtained in step (1) into a high-pressure reactor and keeping the temperature to obtain a sample; (3) The sample obtained in step (2) is washed with anhydrous ethanol and separated to obtain an anhydrous proton conductive electrolyte material of the supramolecular metal halide framework.
[0005] Preferably, the hydrohalic acid is one of hydroiodic acid and hydrobromic acid, or any combination of the two.
[0006] Preferably, the anhydrous proton conductive electrolyte material of the supramolecular metal halide framework in step (3) is (4-Apy)BiI x Br 4-x , exists in the form of x = 0-4.
[0007] Preferably, the proton conductivity of the anhydrous proton conductive electrolyte material of the supramolecular metal halide framework in step (3) at 140°C is σ=2.45×10 −4 S cm −1 -1.54×10 −3 S cm −1 .
[0008] Preferably, in step (1), the molar ratio of Bi2O3 to 4-Apy is 0.5:1.
[0009] Preferably, in step (1), the amount of saturated hydrohalic acid added is 1 ml when the amount of 4-Apy is 0.001 mol, and the amount of ethanol added is 4 times the volume of the hydrohalic acid.
[0010] Preferably, the high-pressure reactor is a 25 mL Teflon high-pressure reactor.
[0011] Preferably, the insulation temperature is 140° C. and the insulation time is 4 hours.
[0012] The invention discloses an application of an anhydrous proton conductive electrolyte material based on a supramolecular metal halide framework, wherein the material is applied in a direct methanol fuel cell for proton conduction.
[0013] Advantages of the present invention: The anhydrous proton conductive electrolyte material prepared by the present invention has a high conductivity (σ = 1.54 × 10 at 140 °C) −3 S cm −1 ) are competitive with several best-performing anhydrous proton-conducting MOFs / PCPs materials. The systematic results based on SMHFs indicate that proton conduction is a new backbone for metal halide materials and a different approach to proton-conducting solids. − , the crystal system of the compound changes from orthorhombic to monoclinic, and when I is completely replaced by Br, the smallest yellow crystal is generated. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 (a) is (4-Apy)BiIxBr obtained in Example 1-7 4-xX-ray powder diffraction (PXRD) pattern of the material; (b) is the high-resolution PXRD pattern.
[0015] Figure 2 (4-Apy)BiIxBr obtained in Example 1-7 4-x Photographs of materials.
[0016] Figure 3 Example 1-7 (4-Apy) BiI x Br 4-x UV-visible light absorption of materials.
[0017] Figure 4 (a) is the Nyquist plot of (4-Apy)BiI4 material particles at different temperatures, (b) is the temperature-dependent proton conductivity spectrum of (4-Apy)BiI4 material, and (c) is the relationship between log(σT) and 1000 / T of (4-Apy)BiI4 material.
[0018] Figure 5 (a) and (b) are (4-Apy)BiI 3.27 Br 0.73 and Nyquist plots of (4-Apy)BiBr4 material particles at different temperatures, (C) and (D) are for (4-Apy)BiI 3.27 Br 0.73 and (4-Apy)BiBr4 materials temperature-dependent proton conductivity spectra; (e) and (f) are (4-Apy)BiI 3.27 Br 0.73 The relationship between log(σT) and 1000 / T for (4-Apy)BiBr4 materials. DETAILED DESCRIPTION
[0019] Bi2O3 (AR) was purchased from Aladdin; the 4-Apy (AR) was purchased from Aladdin; hydroiodic acid (HI, wt ≥ 47.0%, containing ≤ 1.5% H3PO2 stabilizer) was purchased from McLean Reagent; hydrobromic acid (HBr, 48wt% in H2O) was purchased from Anage Chemical.
[0020] Example 1 A method for preparing an anhydrous proton conductive electrolyte material based on a supramolecular metal halide framework comprises the following steps: (1) 0.233 g Bi2O3, 0.094 g 4-Apy, 1 mL saturated hydroiodic acid and 4 mL ethanol were mixed to obtain a mixture A; (2) Add the mixture A obtained in step (1) into a 25 mL Teflon autoclave and keep it at 140° C. for 4 h to obtain a sample; (3) The sample obtained in step (2) is washed with anhydrous ethanol and separated to obtain an anhydrous proton conductive electrolyte material of a supramolecular metal halide framework; the anhydrous proton conductive electrolyte material of the supramolecular metal halide framework is (4-Apy)BiI4, which is brown in color; the conductivity is measured by an electrochemical workstation using an electrochemical impedance spectroscopy technique, and at 140°C, σ=1.54×10 −3 S cm −1 .
[0021] The impedance spectrum and proton conductivity spectrum of (4-Apy)BiI4 material are shown in Figure 4 As shown, (a) Nyquist plot of (4-Apy) BiI4 material particles at different temperatures. (b) Temperature-dependent proton conductivity spectrum of (4-Apy) BiI4 material. (c) Relationship between log (σT) and 1000 / T of (4-Apy) BiI4 material. The polycrystalline sample of (4-Apy) BiI4 material was ground into a homogeneous powder to prepare particles. The particle diameter was 1 mm and the thickness was about 0.1-0.5 mm. The proton conductivity was removed from the Nyquist plot using the quasi-four-probe method. The charge resistance of proton transport was calculated as follows: The AC impedance analyzer input a sinusoidal AC signal with a frequency range of 1 Hz to 1 MHz and a current of 50 mV. During the test, the sample was placed in an oven and the test temperature was controlled at 20-140°C using a thermometer. The relative humidity during the test was less than 10%. Figure 4 a shows the Nyquist plot (Z′ vs. Z″) of the complex impedance measured on (4-Apy)BiI4 over the temperature range of 20−140 °C. The impedance plot of (4-Apy)BiI4 is typical for materials where ionic conductivity is dominant. The conductivity of (4-Apy)BiI4 was calculated from the impedance values using the following equation: σ = L / ZA, where σ is the conductivity (S cm −1 ), L is the thickness of the sample to be tested (cm), A is the electrode area (cm 2 ), Z is the impedance (Ω). The proton conductivity of the (4-Apy)BiI4 tablet is 1.39 × 10 -4 S cm −1 As the temperature increases, the proton conductivity of SMHF-1 increases, reaching 1.54 × 10 −3 S cm −1 ( Figure 4 b). In addition, the temperature dependence of the proton conductivity of (4-Apy)BiI4 was measured in the temperature range of 20−140°C. The conductivity of (4-Apy)BiI4 increases with increasing temperature, and the activation energy (E a ) is 0.291 eV ( Figure 4c), indicating that the proton conduction behavior is the same as the proton conduction of anhydrous imidazolium hydrosuccinate, in which the proton jumps in the hydrogen bond network.
[0022] Example 2 A method for preparing an anhydrous proton conductive electrolyte material based on a supramolecular metal halide framework comprises the following steps: (1) 0.233 g Bi2O3, 0.094 g 4-Apy, 0.9 mL saturated hydroiodic acid, 0.1 mL saturated hydrobromic acid and 4 mL ethanol were mixed to obtain a mixture A; (2) Add the mixture A obtained in step (1) into a 25 mL Teflon autoclave and keep it at 140° C. for 4 h to obtain a sample; (3) The sample obtained in step (2) is washed with anhydrous ethanol and separated to obtain an anhydrous proton conductive electrolyte material of a supramolecular metal halide framework, which is denoted as SMHF-2. The anhydrous proton conductive electrolyte material of the supramolecular metal halide framework is (4-Apy)BiI 3.87 Br 0.13 , the color is reddish brown; the conductivity was measured by electrochemical workstation using AC impedance spectroscopy technology, at 140℃, σ=1×10 −4 S cm −1 .
[0023] Example 3 A method for preparing an anhydrous proton conductive electrolyte material based on a supramolecular metal halide framework comprises the following steps: (1) 0.233 g Bi2O3, 0.094 g 4-Apy, 0.75 mL saturated hydroiodic acid, 0.25 mL saturated hydrobromic acid and 4 mL ethanol were mixed to obtain a mixture A; (2) Add the mixture A obtained in step (1) into a 25 mL Teflon autoclave and keep it at 140° C. for 4 h to obtain a sample; (3) The sample obtained in step (2) is washed with anhydrous ethanol and separated to obtain an anhydrous proton conductive electrolyte material of a supramolecular metal halide framework, which is denoted as SMHF-3. The anhydrous proton conductive electrolyte material of the supramolecular metal halide framework is (4-Apy)BiI 3.59 Br 0.41 , the color is reddish brown; the conductivity was measured by electrochemical workstation using AC impedance spectroscopy technology, at 140℃, σ=2.45×10 −4 S cm −1 .
[0024] Example 4 A method for preparing an anhydrous proton conductive electrolyte material based on a supramolecular metal halide framework comprises the following steps: (1) 0.233 g Bi2O3, 0.094 g 4-Apy, 0.5 mL saturated hydroiodic acid, 0.5 mL saturated hydrobromic acid and 4 mL ethanol were mixed to obtain a mixture A; (2) Add the mixture A obtained in step (1) into a 25 mL Teflon autoclave and keep it at 140° C. for 4 h to obtain a sample; (3) The sample obtained in step (2) is washed with anhydrous ethanol and separated to obtain an anhydrous proton conductive electrolyte material of a supramolecular metal halide framework, which is denoted as SMHF-4. The anhydrous proton conductive electrolyte material of the supramolecular metal halide framework is (4-Apy)BiI 3.27 Br 0.73 , the color is reddish brown; the conductivity was measured by electrochemical workstation using AC impedance spectroscopy technology, at 140℃, σ=1.0×10 −4 S cm −1 .
[0025] Example 5 A method for preparing an anhydrous proton conductive electrolyte material based on a supramolecular metal halide framework comprises the following steps: (1) 0.233 g Bi2O3, 0.094 g 4-Apy, 0.25 mL saturated hydroiodic acid, 0.75 mL saturated hydrobromic acid and 4 mL ethanol were mixed to obtain a mixture A; (2) Add the mixture A obtained in step (1) into a 25 mL Teflon autoclave and keep it at 140° C. for 4 h to obtain a sample; (3) The sample obtained in step (2) is washed with anhydrous ethanol and separated to obtain an anhydrous proton conductive electrolyte material of a supramolecular metal halide framework, which is denoted as SMHF-5. The anhydrous proton conductive electrolyte material of the supramolecular metal halide framework is (4-Apy)BiI 2.23 Br 1.77 , the color is red; the conductivity was measured by electrochemical workstation using AC impedance spectroscopy technology, at 140℃, σ=1.67×10 −4 S cm −1 .
[0026] Example 6 A method for preparing an anhydrous proton conductive electrolyte material based on a supramolecular metal halide framework comprises the following steps: (1) 0.233 g Bi2O3, 0.094 g 4-Apy, 0.1 mL saturated hydroiodic acid, 0.9 mL saturated hydrobromic acid and 4 mL ethanol were mixed to obtain a mixture A; (2) Add the mixture A obtained in step (1) into a 25 mL Teflon autoclave and keep it at 140° C. for 4 h to obtain a sample; (3) The sample obtained in step (2) is washed with anhydrous ethanol and separated to obtain an anhydrous proton conductive electrolyte material of a supramolecular metal halide framework, which is denoted as SMHF-6. The anhydrous proton conductive electrolyte material of the supramolecular metal halide framework is (4-Apy)BiI 1.09 Br 2.91 , the color is orange; the conductivity is measured by electrochemical workstation using AC impedance spectroscopy technology, at 140℃, σ=1.89×10 −4 S cm −1 .
[0027] Example 7 A method for preparing an anhydrous proton conductive electrolyte material based on a supramolecular metal halide framework comprises the following steps: (1) 0.233 g Bi2O3, 0.094 g 4-Apy, 1 mL saturated hydrobromic acid and 4 mL ethanol were mixed to obtain a mixture A; (2) Add the mixture A obtained in step (1) into a 25 mL Teflon autoclave and keep it at 140° C. for 4 h to obtain a sample; (3) The sample obtained in step (2) is washed with anhydrous ethanol and separated to obtain an anhydrous proton conductive electrolyte material of a supramolecular metal halide framework; the anhydrous proton conductive electrolyte material of the supramolecular metal halide framework is denoted as SMHF-7; the anhydrous proton conductive electrolyte material of the supramolecular metal halide framework is (4-Apy)BiBr4, which is yellow in color; the conductivity is measured by an electrochemical workstation using an electrochemical impedance spectroscopy technique, and at 140°C, σ=2.45×10 −4 S cm −1 .
[0028] Performance Testing (1) The (4-Apy)BiIxBr obtained in Example 1-7 was measured at λ = 0.51704 Å 4-x The X-ray powder diffraction (PXRD) pattern of the material is as follows: Figure 1 As shown, (a) is (4-Apy)BiI x Br 4-x PXRD of solid solution (λ = 0.51704 Å). (b) High-resolution PXRD pattern. The structural composition of the crystal was analyzed using a D8 Advance X-ray powder diffractometer (XRD, Bruker, Germany, Cu Kα ray λ = 0.15404 nm, tube voltage 40 kV, tube current 40 mA, wide-angle scanning range 2θ = 10~80°, step size 0.02°, scanning speed 10° / min); from Figure 1 Powder X-ray diffraction (PXRD) ( Figure 1 a) and high-resolution PXRD patterns ( Figure 1 b). The whole (4-Apy)BiI x Br 4-x The high-resolution PXRD data of the series show that the strongest diffraction peak (hkl =
[110] ) shifts from 2θ = 9.346° (4-Apy)BiI4 to 9.406° (4-Apy)BiI 3.27 Br 0.73 , and then moved to 9.796° (4-Apy)BiBr4. The corresponding interplanar spacing (d) data were calculated using the Bragg equation (2dsinθ=nλ, λ=1.54056), (4-Apy)BiI4, (4-Apy)BiI 3.27 Br 0.73 The d values of (4-Apy)BiBr4 are 9.455, 9.395, and 8.961 Å, respectively, which are consistent with the crystal structure data. 3.27 Br 0.73 In the diffraction pattern, an additional small peak appears at 2θ=7.232°, which is attributed to the diffraction peak of the
[002] (hkl) crystal plane. The appearance of this diffraction peak indicates that the space group of the crystal is changed from orthorhombic to P BCN migrated to the monoclinic P 21 / c. At the same time, with the increase of Br content, the diffraction peak moves to the large angle direction instead of multiple diffraction peaks, indicating that the halogen doping is uniform. The diffraction peak at 4-Apy)BiBr4 moves to 7.603°.
[0029] (2) (4-Apy)BiI obtained in Example 1-7 x Br 4-x Photos such as Figure 2 shown.
[0030] (3) Example 1-7 (4-Apy) BiI x Br 4-x The band gap of Figure 3 As shown, Figure 3 (4-Apy)BiI x Br 4-x UV-visible light absorption. It can be seen from the figure that the band gap of (4-Apy)BiI4 ranges from 1.97eV to 2.85eV of (4-Apy)BiBr4 ( Figure 4 a), (4-Apy)BiI x Br 4-x The band gap increases with the increase of Br content, following Vegard's law.
[0031] (4) Figure 5 (a) and (b) are (4-Apy)BiI 3.27 Br 0.73 Nyquist plots of (c) and (d) for (4-Apy)BiBr4 materials at different temperatures. 3.27 Br 0.73 and (4-Apy)BiBr4 materials; (e) and (f) are temperature-dependent proton conductivity spectra of (4-Apy)BiI 3.27 Br 0.73 The relationship between log(σT) and 1000 / T of (4-Apy)BiBr4 materials. 3.27 Br 0.73 The proton conductivity values of (4-Apy)BiBr4 particle samples at 140 °C are 1.00×10 −4 S cm −1 and 2.45 × 10 −4 S cm −1 (5c, d), which is one order of magnitude smaller than (4-Apy)BiI4 ( Figure 4 b). (4-Apy)BiI 3.27 Br 0.73 and the temperature-dependent σ of (4-Apy)BiBr4 provide activation energies (E) of 0.452 and 0.316 eV for proton transport. a )( Figure 5 e, f).
Claims
1. A method for preparing an anhydrous proton conductive electrolyte material based on a supramolecular metal halide framework, characterized in that: The following steps are included: (1) Bi2O3, 4-Apy, saturated hydrohalic acid and ethanol are uniformly mixed to obtain a mixture A; (2) adding the mixture A obtained in step (1) into a high-pressure reactor and keeping the temperature to obtain a sample; (3) The sample obtained in step (2) is washed with anhydrous ethanol and separated to obtain an anhydrous proton conductive electrolyte material of the supramolecular metal halide framework.
2. The method for preparing an anhydrous proton conductive electrolyte material based on a supramolecular metal halide framework according to claim 1, characterized in that: The hydrohalic acid is one of hydroiodic acid and hydrobromic acid or any combination of the two.
3. The method for preparing an anhydrous proton conductive electrolyte material based on a supramolecular metal halide framework according to claim 2, characterized in that: The anhydrous proton conductive electrolyte material of the supramolecular metal halide framework in step (3) is (4-Apy)BiI x Br 4-x , exists in the form of x = 0-4.
4. The method for preparing anhydrous proton conductive electrolyte material based on supramolecular metal halide framework according to claim 1, characterized in that: The proton conductivity of the anhydrous proton conductive electrolyte material of the supramolecular metal halide framework in step (3) at 140°C is σ=2.45×10 −4 S cm −1 -1.54×10 −3 S cm −1 .
5. The method for preparing anhydrous proton conductive electrolyte material based on supramolecular metal halide framework according to claim 1, characterized in that: The molar ratio of Bi2O3 to 4-Apy in step (1) is 0.5:
1.
6. The method for preparing anhydrous proton conductive electrolyte material based on supramolecular metal halide framework according to claim 1, characterized in that: In step (1), the amount of saturated hydrohalic acid added is 1 ml when the amount of 4-Apy is 0.001 mol, and the amount of ethanol added is 4 times the volume of the hydrohalic acid.
7. The method for preparing anhydrous proton conductive electrolyte material based on supramolecular metal halide framework according to claim 1, characterized in that: The high-pressure reactor is a 25 mL Teflon high-pressure reactor.
8. The method for preparing anhydrous proton conductive electrolyte material based on supramolecular metal halide framework according to claim 1, characterized in that: The insulation temperature is 140° C. and the insulation time is 4 hours.
9. An application of an anhydrous proton conductive electrolyte material based on a supramolecular metal halide framework, characterized in that: The material is used in direct methanol fuel cells for proton conduction, and the material is prepared according to the method of claim 1.